Stigma pada Perempuan Singgle Parent dengan HIV Positif (Studi Kualitatif) - Dewi Damayanti; Rusmala Dewi (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2017)
Living as a single parent woman with HIV poses a variety ofstigmas in the community. Purpose: This study aims to obtain a picture of stigmain single parent women with HIV positive. Methods: This research is a descriptivequalitative research with content analysis approach. Data collection techniqueswere carried out with in-depth interviews conducted on 13 participants. Thesampling technique used was purposive sampling. Data were analyzed withconventional content analysis techniques. Results: The results of the study formed5 themes, namely: experiencing internal stigma, experiencing external stigma anddiscrimination, having children as the highest life motivator, experiencingexcessive physical fatigue, and having problems in starting interactions withpotential life partners new. Conclusion: Single parent women experience doublestigma with status as single parent and HIV positive. Single parent women withHIV need more support, compared to other HIV women, because of the doublestigma felt by participants. The family is the biggest support system for singleparent women, the support and assistance of the family in all things feels verybeneficial for participants.